Psychometric assessment of the US person-centered prenatal and maternity care scales in a low-income predominantly Latinx population in California - Patience A. Afulani; Kimberly Coleman-Phox; Daisy Leon-Martinez; Kathy Z. Fung; Erica Martinez; Mary A. Garza; Charles E. McCulloch; Miriam Kuppermann (BMC, 2023)
Abstract Objectives To assess psychometric properties of two scales developed to measure the quality of person-centered care during pregnancy and childbirth in the United States-the Person-Centered Prenatal Care (PCPC-US) and Person-Centered Maternity Care (PCMC-US) scales-in a low-income predominantly Latinx population in California. Methods Data were collected from July 2020 to June 2023 from surveys of low-income pregnant and birthing people in Fresno, California, participating in the "Engaging Mothers and Babies; Reimagining Antenatal Care for Everyone" (EMBRACE) trial. Research staff administered the 26-item PCPC-US scale at 30-34 weeks' gestation (n = 315) and the 35-item PCMC-US scale at 10-14 weeks after birth (n = 286), using the language preferred by the participant (English or Spanish). We assessed construct, criterion, and known group validity and internal consistency of the scales. Results 78% of respondents identified as Latinx. Factor analysis identified one dominant factor for each scale that accounted for over 60% of the cumulative variance, with most items loading at > 0.3. The items also loaded adequately on sub-scales for "dignity and respect," "communication and autonomy," and "responsive and supportive care." Cronbach's alpha for the full scales were > 0.9 and between 0.70 and 0.87 for the sub-scales. Summative scores range from 0 to 100, with higher scores indicating higher person-centered care. Correlations with scores on scales measuring prenatal care quality and birth experience provided evidence for criterion validity, while associations with known predictors provided evidence for known-group validity. Conclusions The PCPC-US and PCMC-US scales, which were developed using a community-engaged process and found to have good psychometric properties in a largely high-income sample of Black women, were shown to also have good psychometric properties in a sample of low-income primarily Latinx women. Both scales provide valid and reliable tools to measure person-centered care experiences among minoritized communities to support efforts to reduce existing birth inequities.